Sequential changes in urinary biomarker levels in patients with cirrhosis and severe hepatorenal syndrome. (5th October 2021) - Solé, Cristina; Ma, Ann T.; Solà, Elsa; Carol, Marta; Fabrellas, Núria; Juanola, Adrià; Napoleone, Laura; Gratacós‐Ginès, Jordi; Bassegoda, Octavi; Cervera, Marta; Pérez, Martina; Rubio, Ana Belén; et al.
Abstract: Whether tubular injury develops in patients with acute kidney injury owing to hepatorenal syndrome (AKI‐HRS) is controversial. We performed repeated measurements of biomarkers of tubular injury during a 14‐day period in 60 patients with cirrhosis and AKI (34 with AKI‐HRS meeting the classical definition of type 1 HRS and 26 with AKI owing to acute tubular necrosis, AKI‐ATN). Nineteen of 34 patients had resolution of AKI‐HRS, while the remainder had persistent AKI‐HRS. The persistence of AKI‐HRS was associated with remarkably high short‐term mortality. There were no significant differences in urinary NGAL or IL‐18 between patients with resolution vs those with persistent AKI‐HRS throughout the 14‐day period. By contrast, biomarker levels were significantly lower in AKI‐HRS, even if persistent, compared to AKI‐ATN. These findings are highly suggestive of lack of significant tubular injury in AKI‐HRS and could be of value in the clinical decision between combined liver–kidney or liver transplantation alone in patients with cirrhosis and AKI candidates to transplantation.